Design and development of trash trap of stream for mini hydro - Mohd Shaha, Mohd Nashruddin; Ahmad, Faridahanim; Abdullah, Mohd Sufyan; Musa, Mohd Kamaruzaman; Abidin, Nur Izieadiana; Harun, Hasnida; Abdul Hamid, Nor Hazren; Awang, Mariah; Abdul Rahman, Muhammad Ashraf; Hamidon, Nuramidah; Mohamed Yusop, Fatimah; Mustafaa, Mohd Syafiq Syazwan; et al. (2021)
The river became increasingly contaminated over the years and in the wake of rapid development in the town. The purpose of this paper is to invent and provide a trash collector for mini hydro that is readily removable so that the trashes collected can be easily disposed of. Design of the trash trap should be compatible with existing stream structures. Trash trap must prevent any trash and debris from passing through the mini hydro. Fieldwork was done at the stream river to investigate the surrounding and stream structure. The data collected were mass of trash collected with diverter and without diverter. A total of 10.0 kg of trashes were collected. The efficiency of the trash trap was calculated by the proportion of the average mass of diverted trashes by the total mass of trapped trashes. The targeted efficiency for this trash trap project is 70.0%. Based on the data collected, the efficiency of this trash trap is 84.12%. The targeted efficiency was achieved and design improvement of this trash trap will be discussed at the recommendation. In conclusion, the trash trap had been proven as a potential solution for the mini hydro machine problem, diverts and prevents most of the trashes from entering the mini hydro and blocked the turbine from rotating.